Intravascular Imaging Findings After PCI in Patients With Focal and Diffuse Coronary Artery Disease - Hirofumi Ohashi; Takuya Mizukami; Jeroen Sonck; Frederic Bouisset; Brian Ko; Bjarne L. Nørgaard; Michael Mæng; Jesper Møller Jensen; Koshiro Sakai; Hirohiko Ando; Tetsuya Amano; Nicolas Amabile; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Following percutaneous coronary intervention (PCI), optical coherence tomography provides prognosis information. The pullback pressure gradient is a novel index that discriminates focal from diffuse coronary artery disease based on fractional flow reserve pullbacks. We sought to investigate the association between coronary artery disease patterns, defined by coronary physiology, and optical coherence tomography after stent implantation in stable patients undergoing PCI. Methods and Results This multicenter, prospective, single‐arm study was conducted in 5 countries (NCT03782688). Subjects underwent motorized fractional flow reserve pullbacks evaluation followed by optical coherence tomography‐guided PCI. Post‐PCI optical coherence tomography minimum stent area, stent expansion, and the presence of suboptimal findings such as incomplete stent apposition, stent edge dissection, and irregular tissue protrusion were compared between patients with focal versus diffuse disease. Overall, 102 patients (105 vessels) were included. Fractional flow reserve before PCI was 0.65±0.14, pullback pressure gradient was 0.66±0.14, and post‐PCI fractional flow reserve was 0.88±0.06. The mean minimum stent area was 5.69±1.99 mm2 and was significantly larger in vessels with focal disease (6.18±2.12 mm2 versus 5.19±1.72 mm2, P=0.01). After PCI, incomplete stent apposition, stent edge dissection, and irregular tissue protrusion were observed in 27.6%, 10.5%, and 51.4% of the cases, respectively. Vessels with focal disease at baseline had a lower prevalence of incomplete stent apposition (11.3% versus 44.2%, P=0.002) and more irregular tissue protrusion (69.8% versus 32.7%, P<0.001). Conclusions Baseline coronary pathophysiological patterns are associated with suboptimal imaging findings after PCI. Patients with focal disease had larger minimum stent area and a higher incidence of tissue protrusion, whereas stent malapposition was more frequent in patients with diffuse disease.